PENINGKATAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DI KELAS - Ujang Tohari (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2021)
Improving the quality of teacher performance in educational institutions is an important thing that needs to be done by institutional leaders. A very important factor, among others, is the application of school culture towards quality improvement. School culture is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the school cultures that must be maintained is the issue of discipline, including the discipline of teachers in class attendance in the teaching and learning process. Efforts to improve the discipline of teachers can be pursued in various ways. This School Action Research (PTS) was tested in the form of applying reward and punishment for teachers at SMK Negeri 1 Kemang, Bogor Regency. This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in the second cycle, teacher discipline in class attendance in the teaching and learning process increased and met the predetermined indicators of 60%. From the results of this study, it can be concluded that to improve teacher discipline in class attendance in teaching and learning activities, it can be done by applying significant stimuli such as reward and pusnishment theory